2019
DOI: 10.35940/ijrte.d7723.118419
|View full text |Cite
|
Sign up to set email alerts
|

Bayesian Time Series Modelling of the Italian Daily Rainfall Data using Mixed Distribution

Muhammad Safwan Bin Ibrahim*,
Abdul Jalal

Abstract: A combination of continuous and discrete elements is referred to as a mixed distribution. For example, daily rainfall data consist of zero and positive values. We aim to develop a Bayesian time series model that captures the evolution of the daily rainfall data in Italy, focussing on directly linking the amount and occurrence of rainfall. Two gamma (G1 and G2) distributions with different parameterisations and lognormal distribution were investigated to identify the ideal distribution representing the amount p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
(45 reference statements)
0
1
0
Order By: Relevance
“…Therefore, scholars have used indirect methods, mainly relying on the rainfall-runoff relation of the basin as well as the decomposition and composition of time series or the hydrological model, which are modified to eliminate the influence of changes and construct stationary time series. Meanwhile, to restore the original hydrological time series, researchers have proposed a series of direct calculation methods, including the mixed distribution (MD) method (Ibrahim, 2019;Singh & Sinclair, 1972), time-variant moment method (Sheu et al, 2017;Zeng et al, 2016), and conditional probability distribution (CPD) method (Singh et al, 2005;Tanaka et al, 2016). Singh and Sinclair (1972) and Waylen and Woo (1982) found that individuals in the extreme value series selected by frequency analysis sometimes did not come from the same population, that is, they did not obey the same distribution.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, scholars have used indirect methods, mainly relying on the rainfall-runoff relation of the basin as well as the decomposition and composition of time series or the hydrological model, which are modified to eliminate the influence of changes and construct stationary time series. Meanwhile, to restore the original hydrological time series, researchers have proposed a series of direct calculation methods, including the mixed distribution (MD) method (Ibrahim, 2019;Singh & Sinclair, 1972), time-variant moment method (Sheu et al, 2017;Zeng et al, 2016), and conditional probability distribution (CPD) method (Singh et al, 2005;Tanaka et al, 2016). Singh and Sinclair (1972) and Waylen and Woo (1982) found that individuals in the extreme value series selected by frequency analysis sometimes did not come from the same population, that is, they did not obey the same distribution.…”
Section: Introductionmentioning
confidence: 99%